الكرامة والإغتراب بحث في ذات إيموهاغ في رواية أنوبيس لإبراهيم الكوني - خنيش,نورالدين (University of Eloued جامعة الوادي, 2023)
ينطلق بحثنا المعنون بــــ: الكرامة والإغتراب بحث في ذات إيموهاغ من رواية أنوبيس للكاتب إبراهيم الكوني حيث نعالج قضية الإغتراب التي عايشها أنوبي منذ نشأته ومحاولته لطرح الأسئلة على "الما"(الأم) التي قدمت له أجوبة لاهوتية دينية المحتوى مما قادنا إلى البحث في الجانب الفلسفي والديني للطوارق، فالكوني يرسّخ عبر الرواية إلى فهم الأسطورة وتناولها في فن الرواية، لنحاول فهم التركيبة الطارقية من خلال أنوبيس ولماذا يخرج مجتمع إيموهاغ إلى الصحراء ولا يقوم على الاستقرار من خلال الأسطورة التي جمعها الكوني، لنعالج قضية المسخ والتحول والكرامة الصوفية في دراستنا هذه والعديد الجوانب التي يتناولها الكوني في فلسفة الصحراء الأسطورية. Abstract: In our research, entitled „Dignity and alienation: a research into the identity of imohaug/Tuareg people from the novel „Anubis‟ by Ibrahim Al-KONI, we address the issue of alienation experienced by the novel‟s protagonist, Anubi, and his attempt to ask his “ma”(mother) questions, who in turn gave him religious and theological answers, her answers led us to investigate the philosophical and religious aspects of the “Tuareg” culture in the novel, Al-Koni establishes an understanding of myth and it‟s uses in the art of the novel, moreover, we try to understand through the author‟s use of myth in the novel and through the protagonist Anubi, the “Tuareg” people‟s social structure and the answer to why they live a nomadic lifestyle, additionally, in our research, we address the issues of metamorphosis, transformation, the dignity of Sufism, and many philosophical aspects Al-Koni deals with in the novel
Keywords: ايموهاغ; أنوبيس; الكرامة الصوفية; الإغتراب; imohaug; the legend; Anubis; Sufi dignity; Alienation